Peningkatan Prestasi Belajar Matematika Tentang Operasi Hitung Pecahan dengan Metode Demonstrasi Kelas V Sekolah Dasar - Aminarti, Aminarti Aminarti (Universitas Sebelas Maret, 2021)
This study aims to improve learning achievement in mathematics about fractionalarithmetic operations with the demonstration method in fifth grade elementary school. Thistype of research is classroom action research. The research was carried out at SD NegeriSusukan 01. The subjects in this study were students of class V-A SD Negeri Susukan 01,Ungaran Timur District, Semarang Regency, in the 2018/2019 academic year, totaling 28children consisting of 15 boys and 13 girls. The research was carried out in the first semesterof the 2019/2020 academic year in two stages of improvement: (a) Repair of cycle 1 wascarried out on 24 and 28 September 2019 and (b) Repair of cycle 2 was carried out on October15 and 19 2019. Based on the results of the demonstration method research very effectivelyused in learning Mathematics proven to improve student learning outcomes. The averageresult of the initial learning is 51.43 with a completeness rate of 28.57%, the first cycle is anaverage of 74.64 with a completeness rate of 71.43%. While the average in the second cycle is82.50 with a completeness rate of 96.43%.